A prebiotic diet based on dandelion (Taraxacum officinale) improves the productive performance and intestinal morphology of laying hens - Canto Saenz, Francys Mitchel (2021)
The inclusion of Dandelion meal [DL] (Taraxacum officinale) in the diet of laying hens and its effect on productive performance, intestinal morphology and dry matter content in feces was evaluated. Ninety-six 35-week-old brown Hisex hens were distributed in 6 treatments. Gradual levels of DM meal (1%, 2%, 3% and 4%) were compared with a diet based on the mixture of antibiotics (CAB; 0.03% Zinc bacitracin + 0.03% colistin sulfate) and another based of 0.20% sodium butyrate (CPB). DM and CPB improved egg production (p < 0.05) compared to CAB, but feed consumption and egg weight decreased with the use of 4% DM (p < 0.05), without affecting the feed conversion ratio (p > 0.05). In general, DM (1% - 4%) improved intestinal morphology parameters (p < 0.05). Higher quantity and content of dry matter in feces was observed in 4% DM compared to CAB. The incorporation of up to 3% DM improved the productive indexes on the feeding of laying hens and managed to have the best prebiotic effect, as it was evidenced in the intestinal morphology and goblet cells.